The image of an ideal politician in the minds of Russian youth - A. A. Komarova (Вестник университета)
The image of a political leader through the eyes of modern youth is considered. The image of a politician is a reflection in the mass consciousness of an emotionally colored idea of politicians. A survey of young people aged 15 to 29 years who live permanently in Moscow was conducted. In order to create a portrait of an ideal political leader, respondents were offered several lists of qualities and characteristics that, in the opinion of young people, a modern politician should possess. It was determined the five main qualities of the “ideal politician”: charisma, publicity, openness of personal life, views, availability of professional education, the ability to empathize, loyal attitude to subcultures and minorities. The study of the image of the ideal political leader allows building a dialogue with the youth audience and getting the material necessary for the formation of a positive image of a real politician.